Why Choose Kampung Inggris? Analysis of Factors Driving English Learners' Interest in Pare - M Bambang Purwanto; Yuliana; Marsinah; Despita (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Kampung Inggris Pare has become the largest English-learning center in Indonesia, attracting thousands of learners from diverse regions and backgrounds. However, the main factors that drive them to choose English Village over other course institutions have not been studied in depth. This study aims to analyze these factors and identify the dominant factors in learners' decisions. This study uses a qualitative descriptive method with a case study approach, involving 40 learners as research subjects. Data were collected through questionnaires, interviews, and observations, and then analyzed using quantitative and qualitative descriptive approaches. The study's results show that intensive learning methods, supportive environments, and affordable costs are the main factors that attract learners. The conclusion of this study confirms that the Kampung Inggris has unique advantages that are difficult to find in other course institutions.